Exosomes Derived From Heat Stroke Cases Carry miRNAs Associated With Inflammation and Coagulation Cascade - Li, Yue; Wen, Qiang; Chen, Huaisheng; Wu, Xinhui; Liu, Bin; Li, Hui; Su, Lei; Tong, Huasheng (Frontiers in Immunology, 2021)
The pathological mechanism underlying heat stroke (HS) is associated with the dysbalanced inflammation and coagulation cascade. Cell-derived circulating extracellular vesicles (EVs), as a novel pathway mediating intercellular communication, are associated with the immune response and inflammation in critical inflammatory syndromes, such as sepsis. Although these vesicles contain genetic material correlated with their biological function, their molecular cargo during HS remains unknown. In this study, we evaluate the presence of microRNAs (miRNAs) and messenger RNAs (mRNAs) associated with inflammatory responses and coagulation cascade in exosomes of patients with HS. Blood samples were collected from three patients with HS at the time of admission to the intensive care unit; three healthy volunteers were selected as control. Exosomes were isolated using ultracentrifugation, and their miRNA content was profiled using next-generation sequencing; mRNA content was evaluated using qPCR array. Compared with those from healthy volunteers, exosomes from patients with HS showed substantial changes in the expression of 202 exosomal miRNAs (154 upregulated and 48 downregulated miRNAs). The most upregulated miRNAs included miR-511-3p, miR-122-5p, miR-155-3p, miR-1290, and let7-5p, whereas the most downregulated ones included miR-150-3p, 146a-5p, and 151a-3p. Gene ontology enrichment of the miRNAs of patients with HS compared with control subjects were associated mostly with inflammatory response, including T cell activation, B cell receptor signaling, dendritic cell chemotaxis and leukocyte migration, and platelet activation and blood coagulation. The identified miRNAs were primarily enriched to the signal transduction pathways namely, T cell receptor signaling, Ras signaling, chemokine signaling, platelet activation, and leukocyte transendothelial migration, all of which are associated with inflammation and hemostasis. Multiple targeted mRNAs associated with the inflammatory response, blood coagulation, and platelet activation were further verified in serum exosomes. Exosomes from patients with HS convey miRNAs and mRNAs associated with pathogenic pathways, including inflammatory response and coagulation cascade. Exosomes may represent a novel mechanism for intercellular communication during HS.